Virgin's stolen nights with the boss - Marinelli, Carol (Marinelli, Carol. Heirs to the Romero empire., 2023)
"Brilliant equestrian and heiress Carmen Romero abandoned her privileged life to make her own way in the world. Hired by sinfully attractive polo player Elias Henley as a stable hand, Carmen feels more comfortable covered in straw than she ever did draped in diamonds. Elias rarely spares a glance for his staff, until Carmen. And he has no intention of resisting their attraction! Playboy Elias knows he'll give the innocent all the pleasure she could want, but that's it. Unless their passion can unlock a connection much harder to walk away from..."--